Thermodynamic and energy analysis of renewable butanol–ethanol fuel reforming for the production of hydrogen. Issue 6 (December 2017) - Kumar, Brajesh; Kumar, Shashi; Kumar, Surendra
Highlights: SRB, SRE and SRB-E processes are simulated for H2 production. Production of H2 is high in steam reforming of butanol. Carbon formation is highly reduced in steam reforming of B-E mixtures. Energy requirement per mol of H2 production is reduced in SRB-E process. Thermal and exergy efficiencies are higher in SRB-E and SRE processes. Abstract: The butanol-ethanol (B–E) mixture with water, obtained from ABE (Acetone-Butanol-ethanol) fermentation, is utilized as a renewable biofuel for the production of clean energy carrier hydrogen by steam reforming process (SRB–E). The thermodynamic analysis of steam reforming process for B–E mixture is carried out by Gibbs free energy minimization method. The thermal and exergy efficiencies for the process are investigated to exploit the potential of B–E mixture for hydrogen production. For performance evaluation, the variational trends of moles of products (H2, CO, CO2, CH4, and carbon) are studied at equilibrium as a function of temperature (573–1473 K), pressure (1–10 atm), steam/fuel molar feed ratio (0–12) for composition of B–E mixture (50 to 90% B). For mixture (90% B), the maximum production of H2 (9.555 mol per mol of fuel) is achieved at 973 K temperature, 1 atm pressure, molar feed ratio of 12. Methane and carbon formation are negligible at high temperature (>873 K) and molar feed ratio (>5) for all B–E compositions. Energy required per mol of H2 is 50.77 kJ/mol for mixture (90% B) and is lower than that for steam reforming of butanol. The thermal efficiency is 70.071%, close to maximum for mixture (90% B), which is higher than butanol (69.885%), and ethanol (68.491%). For 90% B mixture, exergy efficiency (48.582%) is also comparable with that of butanol (48.693%) and ethanol (46.145%). This study proposes an economic process for hydrogen production via steam reforming of B–E mixture directly.